(GeTe)x–(Sb2Te3)1–x phase‐change thin films as potential thermoelectric materials. Issue 1 (26th September 2012) - Sittner, Ernst‐Roland; Siegert, Karl Simon; Jost, Peter; Schlockermann, Carl; Lange, Felix Rolf Lutz; Wuttig, Matthias
Abstract Phase‐change materials form a unique material class, characterized by a rather unusual combination of physical properties. Exhibiting fast crystallization and a large contrast in optical reflectivity and electrical conductivity between the amorphous and the crystalline state, they are ideally suited for non‐volatile data storage. Here, we present the thermoelectric properties of Ge3Sb2Te6 and Ge8Sb2Te11 phase‐change alloys measured between room temperature and 120 °C. Both systems display intrinsically high Seebeck coefficients and low thermal conductivities. While low electrical conductivities preclude the employment of Ge3Sb2Te6 in thermoelectric applications, the GeTe rich Ge8Sb2Te11 exhibits high ZTs of up to 0.7 in the temperature range investigated, which renders this alloy a potential p‐type thermoelectric material.